Estimating heritability of glycaemic response to metformin using nationwide electronic health records and population-sized pedigree - Iris N. Kalka (Nature Portfolio, 2021)
Kalka and Gavrieli et al. assessed the heritability of variation in the glycaemic response to metformin by leveraging electronic health records data gathered from a large cohort of patients with diabetes and combining it with pedigree information. The authors show that although the variability in this response has a heritable component, most of it is likely non-genetic.